Muc-1 Family Tumor Markers and Their Role in the Diagnosis of Breast Cancer, Review Article - Mansour Kargar; Reza Fardid; Ali Farhadi (Fasa University of Medical Sciences, 2022)
Background & Objective: Tumor markers are elements produced by tumors or other cells in the body in response to cancer or some benign condition. Although most of these markers are made by normal cells as well as cancer cells, they are produced at much higher levels in cancerous conditions. This study aimed to provide a method for using tumor markers to diagnose cancer and detect the presence of metastasis and recurrence of the disease. Materials & Methods: The present narrative review study was done by selecting the appropriate keywords and searching for research and review studies indexed in Google Scholar, PubMed, Science Direct, and SID databases. Results: These studies often indicate the effective role of tumor markers in the MUC-1 family (especially Cancer antigen15-3(CA15-3)) and CEA (carcinoembryonic antigen) as the most widely used tumor markers in patients with breast cancer. Conclusions: Based on information from studies on tumor markers, the combination of CEA, CA15-3, PRL (prolactin), KL-6(Kerbs von den Lungen), Thioredoxin 1, and FER (ferritin) tumor markers can increase the sensitivity of early-stage breast cancer detection, and CA15-3 tumor markers can also be used to identify the presence or absence of metastasis to the axillary lymph nodes. The use of ultrasound (especially color Doppler) and its combination with CEA and CA15-3 tumor markers are recommended to improve the accuracy of a breast cancer diagnosis.